An Emotioncy-Based Investigation into Students and Teachers’ Satisfaction with the Content of the Persian Language History Books - Zahra Jahani; Shima Ebrahimi; Samira Bameshki (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Emotioncy, coined from the combination of emotion and frequency, focuses on emotions evoked by the senses from which we receive inputs, hence learning happens. The importance of emotioncy in designing coursebooks cannot be ignored. Drawing on the levels of emotioncy, the present study aims to assess the level of students and teachers’ satisfaction with the content of Persian language history books. In doing so, 150 students majoring in Persian Language and Literature were invited from 14 universities to fill in an emotioncy questionnaire, developed by the authors. The attitudes of eight teachers with regard to their satisfaction with the book content were gathered by semi-structured interviews. The analysis of the questionnaire data indicates that the Visual factor and Inner factor received the highest and lowest levels of students’ satisfaction (i.e. 14.57 & 8.00), respectively. As a result, the students were not generally satisfied with the book content. The teachers mentioned that the books have failed to take into account emotions, despite their importance. It appears that the employment of emotioncy in drafting coursebooks on the history of the Persian language could facilitate learning for students as they become emotionally engaged with the teaching content, hence the learned materials are easily transferred to permanent memory.